HIV Disease Impact on Mothers: What They Miss During Their Children’s Developmental Years - Murphy, Debra A. (Springer US, 2010)
Adjusting to chronic illness is very complicated for families with children, as they are already faced with the challenge of development and childrearing. In this study, qualitative interviews were conducted with HIV positive mothers on a number of issues related to being an HIV positive mother raising young children. One topic of the interview was whether or not they felt that HIV had caused them to miss activities with their children while the children were growing up, what types of activities they had missed, the age of the child for each example, and how HIV had led to missing these activities. Interviews were conducted in 2008 with a random sample of 57 mothers being followed in a longitudinal assessment study. All study participants were English or Spanish speaking. Mean age was 44.1 (SD = 5.6) years; 47% were Latina; 35% African American; 11% White; and 7% other race. About 60% of the mothers disclosed that their HIV status had caused them to miss out on activities with their children while their children were growing up, ranging from daily care activities to major school and extra-curricular activities. Some mothers missed significant amounts of time with their children due to hospitalizations. In some cases mothers felt forced into a choice between mothering ability and their own health, including adherence to medications. Implications for the mothers and the children are discussed.